Charge‐Compensated Metallacarborane Building Blocks for Conjugation with Peptides. (15th January 2016) - Frank, René; Ahrens, Verena M.; Boehnke, Solveig; Beck‐Sickinger, Annette G.; Hey‐Hawkins, Evamarie
Abstract: The cobalt bis(dicarbollide) complex [ commo ‐3, 3′‐Co(1, 2‐C2 B9 H11 )2 ] − has captured much attention in biochemical and medical contexts, in particular for the treatment of tumors by boron neutron capture therapy (BNCT). Derivatives of cobalt bis(dicarbollide) are commonly prepared through ring‐opening reactions of cyclic oxonium ions, so the corresponding products are usually charged. Furthermore, attempts to incorporate cobalt bis(dicarbollide) into peptides are rare, despite obvious potential advantages. Here the synthesis of an imidazolium‐based charge‐compensated cobalt bis(dicarbollide) building block, which allows additional modifications with moieties of biochemical relevance, such as monosaccharides, is reported. Furthermore, conjugates of these building blocks with the Y1 ‐receptor‐selective derivative of neuropeptide Y ([F 7, P 34 ]‐NPY) retained excellent response to hY1 receptors found to be overexpressed in breast tumors and metastases. Abstract : Selective accumulation of boron in tumor cells : Conjugates of imidazolium‐based charge‐compensated cobalt bis‐ (dicarbollide) building blocks with the Y1 ‐receptor‐selective derivative of neuropeptide Y ([F 7, P 34 ]‐NPY) retained excellent response to hY1 receptors found to be overexpressed in breast tumors and metastases.